Pengaruh Agregat Kasar Batu Kali Manggaran Dan Batu Pecah Tapa Utama Terhadap Kuat Tekan Beton Pada Bangunan Struktur - wati, Tisna; Firman, Annas; Kumalasari, Dwi; Annasir, Muhammad Abdul Malik; Rabbani, Nauval; Syakifudin, Riza; Alfin, Yusuf (Universitas Teuku Umar, 2024)
Abstract Good quality concrete is concrete whose basic ingredients are also of good quality. One of the ingredients that make up concrete that determines the compressive strength of concrete is coarse aggregate. Coarse aggregate itself is a resource that is easy to obtain, widely available in nature and in various types. According to its origin, coarse aggregate used as a building material for concrete can be divided into two, namely natural aggregate obtained from rivers and artificial aggregate obtained from crushed stone. This research was carried out using 3 variations, namely 100% Kali Manggaran stone, 100% Tapa Utama crushed stone, and a combination of 50% Manggaran 50% Tapa Utama with a plan to use concrete quality K225 or 18.68 MPa, according to the minimum requirements of the concrete quality plan for structural work. The results of the research show that the use of 100% Manggaran river stone at a concrete age of 14 days is 14,834 MPa and 18,117 MPa. Meanwhile, the use of 100% crushed stone tapa Utama obtained a concrete compressive strength of 17,256 MPa at a concrete age of 14 days and 21,045 MPa at an age of 28 days and was in accordance with the planned concrete quality. The maximum compressive strength is the 100% crushed stone tapa Utama concrete variation with a concrete age of 28 days. Keywords: Coarse Aggregate, Compressive Strength of Concrete, Manggaran River Stone, Tapa Utama Crushed Stone